Accounting Information On Earnings Management Practices As Investment Decisions - Nafisatul Aini Al Kifli; Pujiono, Pujiono (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This study aims to determine the effect of accounting information in the form of earnings management on investment decisions. The type of research used is quantitative research using secondary data. The population used is manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange (IDX) 2019-2023 as many as 110 samples. With the data used in this study are financial statements and company stock prices. The results showed that earnings management has an effect on stock prices. Thus, this research can be used by investors as one of the information for making investment decisions.